PENGARUH KEPEMIMPINAN KEPALA DESA DAN PARTISIPASI MASYARAKAT TERHADAP PEMBANGUNAN DESA CEMBA KECAMATAN ENREKANG KABUPATEN ENREKANG - Nurhayani Nurhayani (PRAJA: Jurnal Ilmiah Pemerintahan, 2018)
The purpose of research is to determine the effect Role of the Village Consultative over planning in the Village Cemba District of Enrekang, to know the effect of Community Participation on development planning in the Village Cemba District of Enrekang to Know Effect Position Village Consultative Body and Participation communities to development planning in the Village Cemba District of Enrekang. Types of research using quantitative descriptive, The population in this research is the whole village cemba as many as 1.731 people, and the study sample as many a 95 people. Data collection techniques used in this research is to use the technique (1) observation, (2) interview, (3) questionnaire, and (4) Research Library. The collected data is thn analyzed using frequency tables using skala likert.This study has shown that the influence of leadership on development in rural villages cemba 44,4% or categorized considerable influence, the influence of public participation in the development of rural cemba by 41% or categorized quite influence, and the influence of the leadership of village heads and community participation in the development of rural districts cemba enrekang 44,4% or categorized quite influence.